2007
DOI: 10.1016/j.virol.2007.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelators ICL670 and 311 inhibit HIV-1 transcription

Abstract: HIV-1 replication is induced by an excess of iron and iron chelation by desferrioxamine (DFO) inhibits viral replication by reducing proliferation of infected cells. Treatment of cells with DFO and 2-hydroxy-1-naphthylaldehyde isonicotinoyl hydrazone (311) inhibit expression of proteins that regulate cell-cycle progression, including cycle-dependent kinase 2 (CDK2). Our recent studies showed that CDK2 participates in HIV-1 transcription and viral replication suggesting that inhibition of CDK2 by iron chelators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 39 publications
7
82
0
Order By: Relevance
“…The expression of p21 was also shown to be increased by HIF-1␣, which displaced c-myc on the p21 promoter (43). We previously demonstrated that the iron chelators 311, ICL670, Bp4eT, and Dp4eT inhibit the activity of CDK2 (15,16). Here we showed that PPY-based iron chelators inhibited cell cycle progression of promonocytic THP-1 cells, CEM T cells, and epithelial 293T cells.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The expression of p21 was also shown to be increased by HIF-1␣, which displaced c-myc on the p21 promoter (43). We previously demonstrated that the iron chelators 311, ICL670, Bp4eT, and Dp4eT inhibit the activity of CDK2 (15,16). Here we showed that PPY-based iron chelators inhibited cell cycle progression of promonocytic THP-1 cells, CEM T cells, and epithelial 293T cells.…”
Section: Discussionmentioning
confidence: 59%
“…While we could not detect changes in the p21 expression levels, our previous studies suggested that CDK2 activity is reduced by chelator-treated cells (15,16). To determine whether the PPY-based iron chelators inhibit CDK2 activity, 293T cells were cultured for 48 h at 37°C in the presence or absence of the iron chelators, using the PPY compound as a control.…”
Section: Effects Of Ppy-based Iron Chelators On Hiv-1 Transcription Imentioning
confidence: 77%
See 1 more Smart Citation
“…The importance of iron for mycobacterial growth suggests a potential role for chelation therapy as a treatment option. Indeed, the use of iron chelation as a potential therapy for infectious diseases has been well documented, including the in vitro use of chelators to inhibit viral replication and reverse transcriptase activity in human immunodeficiency virus treatment (Debebe et al, 2007;Traore and Meyer, 2007). Furthermore, in malarial infection, chelation therapy increased parasite clearance rate (Pradines et al, 2002;Walcourt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…12 However, another study found no change in NF-jB with iron chelation. 13 A reduction in cyclin-dependent kinase (CDK) 2/cyclin E complex activity has also been suggested as one of the mechanisms of how iron deficiency reduces HIV replication, 11,14 but changes in CDK2/cyclin E complex activity were not observed in another study using DFO to decrease cellular iron. 15 Therefore, the interaction between HIV infection and cellular and systemic iron status, particularly in the post-ART era, remains unclear.…”
mentioning
confidence: 99%